2001
DOI: 10.1007/s003950170010
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical and metabolic basis of myocardial blood flow heterogeneity

Abstract: Precise measurements of regional myocardial blood flow heterogeneity had to be developed before one could seek causation for the heterogeneity. Deposition techniques (particles or molecular microspheres) are the most precise, but imaging techniques have begun to provide high enough resolution to allow in vivo studies. Assigning causation has been difficult. There is no apparent association with the regional concentrations of energy-related enzymes or substrates, but these are measures of status, not of metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 100 publications
3
42
1
Order By: Relevance
“…"The value of R rbc is about 0.69 [13][14][15]31,38 . Multiplying [CO 2 ] bl by 22.256 converts the units of molar to ml of CO 2 per ml of blood.…”
Section: Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…"The value of R rbc is about 0.69 [13][14][15]31,38 . Multiplying [CO 2 ] bl by 22.256 converts the units of molar to ml of CO 2 per ml of blood.…”
Section: Correctionmentioning
confidence: 99%
“…This reduces the computation time by about a factor of 20 compared to solving the Adair-type equations by iteration. 26 Computational efficiency is a major issue in analyzing the data from PET imaging studies of tracer-labeled 15 O-oxygen because of the broad heterogeneity of flows and metabolism in the heart (e.g., see King et al, 47 Caldwell et al, 24 reviews by Bassingthwaighte et al 14 The steady-state spatial distribution of regional blood flows within organs is always broad, having coefficients of variation of 25% or more, depending on the tissue under study and the ambient humoral, nervous, and metabolic conditions. 9,47 To allow an approximate description of spatial heterogeneity at the level of spatial resolution of about 0.5-1% of the heart mass (the resolution used for PET analysis) and still account for the heterogeneity within the observed region-of-interest, our capillary-tissue exchange model can be incorporated into a multicapillary configuration in which the blood-tissue exchange regions are composed of a set of parallel, independent capillary-tissue exchange units such as those described.…”
Section: Improvements Over Prior Modelsmentioning
confidence: 99%
“…In parallel work, we have developed a computational model of muscle cell oxidative energy metabolism (illustrated in Fig.·2B), which we have applied to analyze cardiac and skeletal muscle energetics (Bassingthwaighte et al, 2001;Wu et al, 2007). In these studies, ATP consumption is treated as a forcing function and the ATP consuming processes associated with contraction and electrophysiology are not explicitly modelled.…”
Section: The Development Of Integrated Cardiac Modelsmentioning
confidence: 99%
“…While such data-driven models often give useful descriptions and insights into specific data sets, these models often fail when combined together to study interaction between multiple processes. On the other hand, physics-based models -models built on principles including the laws of mechanics and thermodynamics, in which assumptions and approximations are made explicit -operate with a common currency of mass, charge, energy and momentum (Bassingthwaighte et al, 2001;Qian et al, 2003). With care, such models may be naturally integrated together to form comprehensive models of biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Yet it has been observed that local myocardial blood flow can vary regionally by up to 10-fold in vivo [32][33][34][35]. Since oxygen [35] and fatty acid [36] uptake are tightly proportional to regional flow in the myocardium, it is proposed that ATP hydrolysis varies regionally as well.…”
Section: Future Considerationsmentioning
confidence: 99%